The medical impact of hepatitis D virus infection in Uzbekistan. (20th September 2019) - Khodjaeva, Malika; Ibadullaeva, Nargiz; Khikmatullaeva, Aziza; Joldasova, Elizaveta; Ismoilov, Umed; Colombo, Massimo; Caviglia, Gian Paolo; Rizzetto, Mario; Musabaev, Erkin
Abstract: Background & Aims: The hepatitis B virus (HBV) is endemic in Uzbekistan but the medical impact of infection with the HBV‐dependent hepatitis D virus (HDV) is unknown in the Country. An Hepatology Center was recently established at the Institute of Virology in Tashkent, which has set up a database enlisting patients with chronic viral liver disorders from all over Uzbekistan; it provides an observatory on the current scenario of viral hepatitis in the Country. Methods: The prevalence of HBV monoinfection, hepatitis C virus (HCV) infection and HDV superinfection on hepatitis B surface antigen (HBsAg)‐positive cirrhosis was determined in 6589 patients with viral cirrhosis collected in the last 3 years. Results: Of 1089, 1150 and 1455 carriers of the HBsAg with cirrhosis recruited in 2016, 2017 and 2018, 834 (76.5%), 926 (80.5%) and 1224 (84%) respectively, had antibody to the HDV. In 2016, 2017 and 2018, the prevalence of HDV infection has been 41%, 45% and 49.1% respectively, largely exceeding the prevalence of HBV monoinfection (12.5%, 11% and 9.3% respectively) and surpassing the prevalence of HCV in 2017 and 2018 (44% and 41.5% respectively). The median age of the patients with HDV cirrhosis was 39 years, distinctly lower than that of HBV and HCV patients (46 and 55). Conclusions: Superinfection with the HDV is present in over 80% of the HBsAg‐positive cirrhosis in Uzbekistan. The HDV appears to be the major cause of advanced viral liver disease and of juvenile cirrhosis in the Country. Abstract : See Editorial on Page 2034